2016
DOI: 10.1017/cem.2016.383
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of emergency department point-of-care ultrasound for rib fracture diagnosis in minor thoracic injury

Abstract: PoCUS examination appears to be a feasible technique for a rib fracture diagnosis in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Pain during patient assessment was the PoCUS technique’s most important (15%) flaw. In the emergency room, PoCUS examination seems to be a reliable method for rib fracture diagnosis 32 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain during patient assessment was the PoCUS technique’s most important (15%) flaw. In the emergency room, PoCUS examination seems to be a reliable method for rib fracture diagnosis 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, POCUS can be combined with the Ottawa Ankle Rule which are considered as efficient diagnostic tool for assessing ankle and fifth metatarsal bone fractures among 242 patients compared to the plain radiograph 31 . A study evaluating role of POCUS in rib fracture detection among patient with minor thoracic trauma in emergency department revealed higher feasibility along with pain being the primary limiting aspect 32 . POCUS is not only emerging as a promising diagnostic tool in long bone fractures, but also in evaluation of wide variety of fracture characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies from 2017 used the total cases of positive findings of rib fractures found by either LUS or CXR as the criterion standard (assuming that there were no false-positive findings) and found a sensitivity of 81–98% in LUS compared to 41–53% for CXR [73, 74]. A third study found a similar concordance between LUS and CXR and/or CCT [72].…”
Section: Resultsmentioning
confidence: 99%
“…Three non-English language studies were identified and translated. One study was North American,18 six studies were Asian19–25 and five European 7 26–29. A prospective diagnostic test accuracy study design was used in all but one of the included studies, with Martino et al 29 using a case series design 29…”
Section: Resultsmentioning
confidence: 99%